Exploring the Challenges Faced by Students in Learning Writing Recount Text Using Discovery Learning through Short Videos - Jaelaani, Elan; Parmawati, Aseptiana (PROJECT (Professional Journal of English Education), 2025)
The study aims to explore the challenges faced by the tenth-grade students in learning to write a recount text through discovery learning using short video. The study used a descriptive qualitative method approach. Hence, the researcher collected the data by using interviews, observations, and document analysis. And then, the participants who participated in this study were 17 students of a senior high school located in Bandung. After gathering the data, the researcher then analyzed and coded them to make interpretations about the findings. The result revealed that the challenges faced by the students in creating a recount text include limited English proficiency. Additionally, it is recommended for further research to explore other areas like factors that may influence the effectiveness of using discovery learning through short videos in teaching writing recount text.